Pembuatan Sabun Ultra Transparan Berbasis Minyak Kelapa (Virgin Coconut Oil) Melalui Proses Pemanasan (Hot Process) - Hidayat, Ade Nurul; Supriyati, Supriyati; Krismanto, Rendy (DPPM UNIVERSITAS PELITA BANGSA, 2022)
Indonesia is the second largest coconut producing country in the world and demand for coconut products continues to increase both in the export and domestic markets. Coconut oil is one of the most important raw materials for making soap. There are two processes of making soap by saponification reaction, namely hot and cold processes. The purpose of this study was to provide scientific information about the benefits of adding the content of soap making. This research is expected to help improve the economy of coconut farmers in Indonesia. The materials used in this study were VCO, stearic acid, NaOH, glycerin, ethanol (70%), sorbitol solution (66.66%). This experimental research method uses laboratory experimental methods (pH and homogeneity tests) using descriptive analysis (using SPSS), to provide information about the manufacture of this soap product. The hot process method is carried out to streamline the saponification process in soap making so that ultra transparent soap products can be formed properly because the hot process has the advantage of accelerating the saponification reaction process. The results of testing/evaluation of ultra transparent soap products are in accordance with the SNI (1994) standard, namely having a satisfactory level of satisfaction, pH 9.46 and having homogeneity properties.